Analysis of Marriage Customs of the Saluan Ethnic Perspective of Islamic Law in Banggai District - Ismail Ismail; Zainal Abidin; Gasim Yamani (State Institute for Islamic Studies Palu, 2022)
This study aims to analyze the marriage customs of the Saluan Tribe in the perspective of Islamic law in Banggai Regency. The analysis of this research includes the implementation of marriage according to the custom of the Saluan tribe, Banggai Regency and a review of Islamic law on the implementation of the traditional marriage of the Saluan tribe. The research used a qualitative method with data collection techniques used namely observation, in-depth interviews and review of written documents. The data were analyzed using data reduction techniques, data presentation, data verification and drawing conclusions. The results of the study show that the implementation of the traditional marriage of the Saluan tribe in Banggai district begins with the Montoi date or determines the wedding date. Then, the marriage process is continued with exploratory (popitoi), proposed marriage (Monsodoi), marriage deliberation (Mobisalakon Saibatanggo). The final process of the traditional marriage of the Saluan tribe is escorting the bride (Menggundulkan Mangantokon) to the man to get married (Akad Nikah) and visit the parents-in-law's house (Mobilangi Tama).The traditional marriage of the Saluan tribe from the perspective of Islamic law is in accordance with Islamic law. When viewed from a maqâṣidalshariah perspective, the marriage process of the Saluan tribe also does not violate Islamic law because the purpose of the traditional marriage procession is to preserve life and property. This research contributes to people's understanding of the history or origins of the Saluan tribal traditional marriage tradition. Then this research can also contribute to the preservation of the customs of the Saluan tribe regarding marriage.